Major Achievements and Future Key Fields of Soil Erosion Research in China - Zhang Keli; Cai Qiangguo; Ke Qihua (Shuitu baochi tongbao)
[Objective] The developing history of soil erosion research in China was reviewed, the major research achievements were summarized, and the current problems and key research fields in the future were analyzed to provide a reference for China's soil and water conservation, regional ecological construction, and high-quality green development. [Methods] Based on years of work experiences from field investigations and academic research on soil erosion, long-term consideration has been given to major issues related to soil erosion in China through numerous academic discussions and communications with leading experts. [Results] A series of major research achievements have been obtained in the field of soil erosion in China during the last one hundred years, but there have also some drawbacks and problems. In the future, soil erosion research in China should focus on several key fields, such as the improvement, promotion, and accuracy evaluation of soil erosion prediction models; calculation methods and model construction for slope runoff; evaluation of the representativeness and validity of results from simulated rainfall and flume scouring experiments; and so on. More attention should be given to the mechanisms of soil erosion processes, model applications, technical methods, response evaluations, bottleneck problems, and other issues. [Conclusion] Researches over the past century has shown that soil erosion research should be conducted based on national conditions. Symbolic achievements could only be achieved by determining and adjusting research directions according to the characteristics of soil erosion, the research status, and the changes in social demands in China. Meanwhile, in the new era when the country is vigorously promoting the construction of ecological civilization, soil erosion research must be refreshed with new ideas and emphases. Moreover, soil and water conservation practices should also be integrated with rural revitalization and ecological construction by giving priority to soil erosion prevention and reducing disturbance to soil. Besides, we should change the previously used model of instituting laws and regulations after soil destruction and water loss occurred.